Analysis of the Effect of Earnings Management on Audit Service Fees in Five ASEAN-5 Countries (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2020)
This research aims to provide empirical evidence about the effect of earnings management on the audit fee spent by listed firms in ASEAN-5.Â This research was conducted using regression analysis with sample of 5.396 firm year listed in ASEAN countries, such as Indonesia, Malaysia, Philippines, Singapore, and Thailand from 2010-2014. The result of this study indicates that earnings management will increase audit fee. It isÂ due toÂ earnings management increase inherent risk faced by auditor.